Respuesta :

The value of the expression is -6 where the expression is given as: ab^2 + c and the values of the variables are a = −3, b = −2, and c = 6

How to evaluate the expression?

The expression is given as:

ab^2 + c

And the values of the variables are

a = −3, b = −2, and c = 6.

Substitute a = −3, b = −2, and c = 6 in ab^2 + c

So, we have

ab^2 + c = (-3) * (-2)^2 + 6

Evaluate

ab^2 + c = -6

Hence, the value of the expression is is -6 where the expression is given as: ab^2 + c and the values of the variables are a = −3, b = −2, and c = 6.

Read more about expressions at:

https://brainly.com/question/723406

#SPJ1

Possible question

Evaluate ab^2 + c  If  a = −3, b = −2, and c = 6.